Analisis Manajemen Kinerja Koordinasi Relasional Tim Pelayanan Terpadu Satu Pintu (Studi Di Kabupaten Maybrat, Provinsi Provinsi Papua Barat Daya) - Kareth, Antoneto; Iriani, Nisma; Putera, Wahyudi; M, Abdul Rahman (Movere Journal, 2025)
The purpose of the study was to determine the quality of relational coordination of the one-stop integrated service team in Maybrat Regency and analyse the relationship between the quality of relational coordination performance and the quality of team elements which include: longevity, clarity of team boundaries, mutual trust, appreciation or recognition. The research was conducted at the Office of Investment and One-Stop Integrated Services (Case Study in Maybrat Regency, Southwest Papua Province). The population of this study is all individuals (individuals) whose characteristics are involved in the sense of participating and interacting directly with other participants in the licensing service work process in the one-stop integrated service team using the census method. Data collection techniques through census techniques (N = 30), with interview methods guided by Likert interval scale structured questionnaire instruments, as well as observation support and document review using SPSS Ver.-23 software program. The analysis results show that the team's current relational coordination performance index is good (weighted mean score 3.66, IKR = 73.2). Relational coordination performance is highly correlated with team elements (r = 855 Sig. 0.001). Team element variables together can explain relational coordination performance by 77 per cent. Two team elements, viz: longevity and mutual trust have significant contributions respectively with t-count = 5.89 at Sig level 0.001 and t-count = 2.585 at Sig level. 0,02. While the other two team elements: clarity of team boundaries and reward or recognition have a positive correlation, but do not have a significant contribution to relational coordination performance. The implications of this research suggest that in order to improve relational coordination performance, it is necessary to periodically carry out team performance evaluations which are followed up by holding socialisation or training for team members at the same time, financial and non-financial rewards are given to team members according to their respective performance. It is also suggested that in the employee rotation policy, the stability of team members needs to be considered.